MATERIAL SELECTION AND MECHANICAL PROPERTIES IN LEAF SPRING APPLICATION: A REVIEW - Utami, Nurhabibah Paramitha Eka; Mahendra, Nanda Yusril; Akbar, Imam; Gunawan, Gunawan; Romli, Romli; Fatoni , Zulkarnain; Pratiwi, Diah Kusuma (Politeknik Negeri Sriwijaya, Indonesia, 2022)
In the industrial world, leaf springs are an important component of vehicles. Therefore, material selection is very influential in producing good mechanical properties that can affect leaf spring performance. In this review article, the author aims to review and compile articles on relevant previous studies to compare the best alternative materials other than steel that meet the criteria for the application of leaf springs. The review method used in this article is to search for articles that are relevant to the keyword material, leaf springs, and mechanical properties. After that, the author will collect articles and choose articles that have the criteria to be reviewed. Then the articles that meet the criteria will be reviewed by extracting the data to the review table. As a result, 24 articles will be reviewed. Then the author will extract data on each article, namely material, tensile strength, and flexure. Flexural and tensile strength are used as quality criteria for each material. The conclusion of the review article obtained is that carbon/epoxy has the potential as an alternative steel material because carbon/epoxy has the highest tensile strength with a value of 1841MPa, and flexural strength with a value of 1646.7MPa is close to steel as shown in the review table. However, further research is needed, such as proper design and more efficient manufacturing methods to produce innovative leaf spring components with high quality and acceptable quality in the industry.